Analysis of the Achievement of the Rapid Action Program for Poverty Alleviation Based on Community Empowerment (A Case Study in Bahoaea Reko-reko and Nambo Villages, Morowali Regency) - Saputra, Ahmad; Tallesang, M.; Lutfi, M.; Jaya, Andi Herman; Yunus, Santi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Poverty eradication is a national priority in line with the 2030 Sustainable Development Goals, which has prompted the Central Sulawesi Provincial Government to launch the Gercep Gaskan Berdaya Programme to strengthen the economic capacity of poor households through community empowerment. This programme targets Morowali as a priority location with the aim of increasing community independence, accelerating poverty reduction, and supporting regional development. This study aims to analyze the effectiveness of the Community Empowerment-Based Poverty Alleviation Program (Gercep Gaskan Berdaya) in Morowali Regency, Central Sulawesi. The program represents a local government strategy to accelerate the reduction of extreme poverty through empowerment and community participation. The research employed a descriptive quantitative method using questionnaires distributed to 22 beneficiaries from Bahoea Reko-Reko Village and Nambo Village. Data were analyzed using simple tabulation, percentage calculation, and mean score comparison. The findings indicate that the program is effective, with an overall average score of 4.11, categorized as good. In Bahoea Reko-Reko Village, the program’s effectiveness is more evident in skill improvement and targeting accuracy, while in Nambo Village it is more dominant in participation and economic sustainability aspects. However, the direct impact on household welfare remains limited, highlighting the need to strengthen household-level interventions. This study recommends enhancing community participation, improving transparency in beneficiary validation, and developing family-based economic empowerment initiatives to ensure program sustainability.